Serial publications in occupational therapy in Latin America - Aleida Fernández Moreno (Cadernos de Terapia Ocupacional, 2012)
This article presents a bibliographic overview on Occupational Therapy journals in four countries:Argentina, Chile, Colombia and Venezuela. Since the beginning of occupational therapy in Latin Americancountries, several training programs at the technical level were created. In the mid 1980s, most courses werereconfigured at the professional level, incorporating researches as a requirement for obtaining the degree. Inthe early years, the literature was built on the supporting basis of the North American production. Most ofthe specific Latin American journals in the area began in the late nineties. It has developed unevenly throughtime, maintaining the greater tradition of publishing books. This paper discusses the beginning, development,decline and resurgence of Occupational Therapy periodicals in Latin American. It was possible to concludethat all efforts are needed to revive the publication of journals specific to the area of occupational therapy anduse digital resources to develop them, aiming at the social appropriation of knowledge and consolidation ofoccupational therapy as a profession.